2017
DOI: 10.1371/journal.pone.0187505
|View full text |Cite
|
Sign up to set email alerts
|

New evidence showing that the destruction of gut bacteria by antibiotic treatment could increase the honey bee’s vulnerability to Nosema infection

Abstract: It has become increasingly clear that gut bacteria play vital roles in the development, nutrition, immunity, and overall fitness of their eukaryotic hosts. We conducted the present study to investigate the effects of gut microbiota disruption on the honey bee’s immune responses to infection by the microsporidian parasite Nosema ceranae. Newly emerged adult workers were collected and divided into four groups: Group I—no treatment; Group II—inoculated with N. ceranae, Group III—antibiotic treatment, and Group IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
96
7
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(120 citation statements)
references
References 67 publications
12
96
7
2
Order By: Relevance
“…The Nosema infection did not significantly alter the composition or quantity of bacteria in the hindgut, probably owing to ‘niche separation’, in which there is minimal interaction between the bacteria of the gut and Nosema spores. In addition to the down‐regulation of the immune system, Li et al () also found that the magnitude of the negative effect of the antibiotics on the health of the bees was greater than that of the Nosema infection; this corroborates findings by Raymann et al () that suggest antibiotic disruption of the bee microbiota is generally harmful. Other studies have found direct antagonism between members of the Ap.…”
Section: Functional Contributions To the Honey Bee Hostsupporting
confidence: 66%
See 2 more Smart Citations
“…The Nosema infection did not significantly alter the composition or quantity of bacteria in the hindgut, probably owing to ‘niche separation’, in which there is minimal interaction between the bacteria of the gut and Nosema spores. In addition to the down‐regulation of the immune system, Li et al () also found that the magnitude of the negative effect of the antibiotics on the health of the bees was greater than that of the Nosema infection; this corroborates findings by Raymann et al () that suggest antibiotic disruption of the bee microbiota is generally harmful. Other studies have found direct antagonism between members of the Ap.…”
Section: Functional Contributions To the Honey Bee Hostsupporting
confidence: 66%
“…There is also evidence that antibiotics may selectively deplete some microbial species more than others, leading to shifts in composition (Gilliam, ; Raymann et al ., ). A study by Li et al () found that Ap. mellifera bees whose microbiota had been eliminated by antibiotics were more susceptible to infection by N. ceranae (a common honey bee pathogen), probably owing to negative impacts on the immune system, as illustrated by a reduction in the expression of genes encoding AMPs.…”
Section: Functional Contributions To the Honey Bee Hostmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies have been correlational (e.g., Hong‐Li et al. , Bosmans et al. ) and the precise mechanisms of how endosymbionts enhance resistance are still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Primers described in previous reports (De Gregoris et al 2011, Powell et al 2014) were used to quantify universal bacteria and phylum-specific Firmicutes . The honey bee β - actin gene was used as a reference (Li et al 2017). The statistical analysis was carried out by unpaired t -test (two-tailed).…”
Section: Methodsmentioning
confidence: 99%